2017
DOI: 10.3389/fneur.2017.00714
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Alterations in Asymptomatic and Symptomatic Patients with Spinocerebellar Ataxia Type 3: A Tract-Based Spatial Statistics Study

Abstract: ObjectiveSpinocerebellar ataxia type 3 (SCA3) is the most commonly occurring type of autosomal dominant spinocerebellar ataxia. The present study aims to investigate progressive changes in white matter (WM) fiber in asymptomatic and symptomatic patients with SCA3.MethodsA total of 62 participants were included in this study. Among them, 16 were asymptomatic mutation carriers (pre-SCA3), 22 were SCA3 patients with clinical symptoms, and 24 were normal controls (NC). Group comparison of tract-based spatial stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 54 publications
8
35
1
Order By: Relevance
“…DTI studies with TBSS have revealed a widespread decrease in FA accompanied by increased AD, RD, and MD in the WM across the whole brain, especially the cerebellum and the brainstem, as well as some supratentorial areas, such as the bilateral frontal, parietal, temporal, and occipital lobes and thalamus, in patients with SCA3/MJD compared with those in controls, as shown in Figure 3 ( Guimarães et al, 2013 ; Nunes et al, 2015 ; Jao et al, 2019 ). What is more, MD increases showed a similar pattern as FA decreases ( Kang et al, 2014 ; Wu et al, 2017 ; Jao et al, 2019 ), and these findings were in line with the results from the multi-atlas segmented findings ( Rezende et al, 2018 ). WM abnormalities were also identified in some fiber pathways that were mostly in the cerebellar connecting tracts, including the pyramidal tract, thalamic radiations, medial lemnisci, corticospinal tract, corticobulbar tract, and corticopontocerebellar tract in patients with SCA3/MJD ( Rezende et al, 2018 ; Jao et al, 2019 ).…”
Section: Diffusion Tensor Imagingsupporting
confidence: 87%
See 2 more Smart Citations
“…DTI studies with TBSS have revealed a widespread decrease in FA accompanied by increased AD, RD, and MD in the WM across the whole brain, especially the cerebellum and the brainstem, as well as some supratentorial areas, such as the bilateral frontal, parietal, temporal, and occipital lobes and thalamus, in patients with SCA3/MJD compared with those in controls, as shown in Figure 3 ( Guimarães et al, 2013 ; Nunes et al, 2015 ; Jao et al, 2019 ). What is more, MD increases showed a similar pattern as FA decreases ( Kang et al, 2014 ; Wu et al, 2017 ; Jao et al, 2019 ), and these findings were in line with the results from the multi-atlas segmented findings ( Rezende et al, 2018 ). WM abnormalities were also identified in some fiber pathways that were mostly in the cerebellar connecting tracts, including the pyramidal tract, thalamic radiations, medial lemnisci, corticospinal tract, corticobulbar tract, and corticopontocerebellar tract in patients with SCA3/MJD ( Rezende et al, 2018 ; Jao et al, 2019 ).…”
Section: Diffusion Tensor Imagingsupporting
confidence: 87%
“…The discovery of the microstructural changes of preclinical SCA3/MJD is helpful to find neuroimaging markers and even predict the clinical onset of disease. Wu et al (2017) identified decreased FA values and increased MD in the cerebellar peduncles of preclinical SCA3/MJD patients. A multi-atlas analysis in another study revealed that all DTI-based parameters were abnormal in the cerebellar peduncles of asymptomatic SCA3/MJD gene carriers ( Rezende et al, 2018 ).…”
Section: Diffusion Tensor Imagingmentioning
confidence: 88%
See 1 more Smart Citation
“…Using TBSS, we identified a pattern of lower FA and higher MD and RD throughout the altered WM tracts. The lower FA and higher MD might indicate abnormal myelin structure, although there are indications that these measures alone are insufficient (Hasan, ; Wu et al, ). In addition, experimental evidence indicates that an increase in RD might reflect myelin damage (Wheeler‐Kingshott & Cercignani, ).…”
Section: Discussionmentioning
confidence: 99%
“…Machado-Joseph disease (MJD) or spinocerebellar ataxia type 3 (SCA3) is a polyQ disease caused by an expanded CAG repeat in the ATXN3 gene 12 that leads to selective dysfunction and loss of neurons of specific nuclei in the cerebellum, brain stem, midbrain, spinal cord, and peripheral nerves [9][10][11][13][14][15][16][17][18][19][20][21] . This central and peripheral nervous system pathology manifests in patients with SCA3 as ataxia and a variable degree of other symptoms, such as extrapyramidal signs, neuropathy, ophthalmoplegia, visual impairment and muscle atrophy [22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%